Effect of leisure activities on cognitive aging in older adults: A systematic review and meta-analysis - Yang, Xinxin; Xu, Xin Yi; Guo, Linlin; Zhang, Yuanyuan; Wang, Shan Shan; Li, Yan (Frontiers in Psychology, 2022)
Abnormal cognitive aging in older adults is a growing public health problem. Previous studies showed inconsistent results pertaining to the effects of leisure activities on cognitive function in older adults. We conducted a systematic review and meta-analysis of published observational longitudinal studies to examine and synthesize the effects of leisure activities on cognitive function in older adults. MEDLINE, PubMed, EMBASE, PsycINFO (Ovid), CINAHL (EBSCO), and Web of Science databases were searched from January 2012 to January 2022. Relative risks (RRs) with 95% confidence intervals (CIs) were pooled using random-effects meta-analysis. Most studies found that leisure activities had a positive effect on cognitive function in older adults. The pooled RR for the effect of leisure activity on cognitive function was 0.77 (95% CI: 0.72–0.81, p < 0.01). The effects of leisure activities on cognitive function varied by different cognitive statuses in older adults, with RRs ranging from 0.55 (95% CI: 0.37–0.83) to 1.07 (95% CI: 0.95–1.22). Meta-regression analysis showed that compared with studies with percentage of female ≥50%, studies with female participant percentage <50% had significantly increased RR (p = 0.01). Moreover, studies conducted in European and American countries had significantly lower RR (p = 0.019), compared with those conducted in Asian countries. Our study revealed different effects of various types of leisure activities on different cognitive statuses in older adults. To make innovative recommendations for promoting cognitive function in older adults, more detailed observational longitudinal studies investigating the effects of different types of leisure activities on different cognitive statuses in older adults are needed.